Flux-cored wire for gas shielded arc welding
Patent Information
- Application Number
- JP2021024643
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-18
- Publication Date
- 2025-03-26
- Estimated Expiration
- 2041-02-18
Smart Images

Figure 0007651313000007 
Figure 0007651313000008 
Figure 0007651313000009
Abstract
Description
[Technical field]
[0001] The present invention relates to a flux-cored wire for gas-shielded arc welding of 490 to 550 MPa class steel, which generates little fume and spatter, particularly when welding at a high current, has excellent welding workability, and can provide a weld metal having good mechanical properties even under welding conditions of high heat input and high interpass temperature. [Background technology]
[0002] In the fields of shipbuilding and steel construction, gas-shielded arc welding in the high current range has been used to improve welding efficiency. High current welding using solid wire for gas-shielded arc welding can increase the amount of deposition per unit time, making it possible to increase the efficiency of welding, but it has problems such as poor welding workability due to an unstable arc, a large amount of spatter generation, and poor bead appearance and shape.
[0003] On the other hand, high current welding using flux-cored wire for gas shielded arc welding has the problem of generating a large amount of fumes as well as a large amount of slag, which makes welding defects such as slag inclusion more likely to occur.
[0004] As a means for solving these problems, development of a solid wire for gas-shielded arc welding with less spatter generation has been carried out. For example, Patent Document 1 discloses a technology that contains rare earth elements, has a solid lubricant on the wire surface, and further has a liquid lubricant film on the outer circumferential surface of the solid lubricant, thereby reducing the amount of spatter generation and improving wire feedability. Patent Document 2 also discloses a solid wire for gas-shielded arc welding that can reduce the amount of spatter generation by forming an alkali metal-impregnated part impregnated with two or more types of alkali metals under the wire surface. However, in high-current welding using a solid wire for gas-shielded arc welding, there is a problem that the amount of spatter generation cannot be sufficiently reduced even if the wire feedability is improved, and the bead appearance and shape cannot be improved because a large amount of spatter is generated.
[0005] On the other hand, flux-cored wires for gas-shielded arc welding that generate less fume have also been developed. For example, Patent Document 3 discloses a technology that can reduce the amount of fume generated by adjusting the C, Ti, and Al in the steel sheath and adding Cs and / or Rb as an alkali metal in the flux. This flux-cored wire is good at reducing the amount of fume generated, but it is not possible to obtain stable weld metal strength and toughness in high-current welding. In addition, since it is a slag-based flux-cored wire, the amount of slag generated is large, so there is a problem that slag inclusion defects are likely to occur.
[0006] In recent years, gas-shielded arc welding solid wires that can handle high heat input and high interpass temperature conditions have been developed to further improve the efficiency of welding, and are specified in JIS Z3312 YGW18. For such gas-shielded arc welding solid wires, the maximum heat input of 40 kJ / cm and the maximum interpass temperature of 350°C are permissible conditions for welding without reducing the strength and toughness of the weld metal, and for high-tensile steel with a tensile strength of 490 MPa, the maximum heat input of 30 kJ / cm and the maximum interpass temperature of 250°C are permissible conditions. For high-tensile steel with a tensile strength of 520 MPa, the maximum heat input of 30 kJ / cm and the maximum interpass temperature of 250°C are permissible conditions.
[0007] As for solid wires for gas shielded arc welding that are compatible with welding conditions of high heat input and high interpass temperature, wires containing Mo, Ti, and B have been proposed, as described in, for example, Patent Documents 4 to 6. With these solid wires, it is possible to ensure the strength and toughness of the weld metal even under welding conditions of high heat input and high interpass temperature, but there are still problems with poor welding workability, such as an unstable arc, a large amount of spatter generation, and poor bead appearance and shape.
[0008] As a flux-cored wire for gas-shielded arc welding that ensures the strength and toughness of the weld metal under welding conditions of high heat input and high interpass temperature and has good welding workability, for example, Patent Documents 7 and 8 disclose flux-cored wires that provide good welding workability and produce weld metal with excellent mechanical properties under welding conditions of high heat input and high interpass temperature. However, these flux-cored wires have a problem of generating a large amount of fumes. In addition, the latter also generates a large amount of slag, which makes welding defects such as slag entrapment more likely to occur. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] JP 2005-169415 A [Patent Document 2] JP 2009-255142 A [Patent Document 3] Japanese Patent Application Publication No. 7-276077 [Patent Document 4] Japanese Patent Application Publication No. 10-230387 [Patent Document 5] JP 2002-346789 A [Patent Document 6] JP 2004-98143 A [Patent Document 7] JP 2005-279683 A [Patent Document 8] JP 2015-205303 A Summary of the Invention [Problem to be solved by the invention]
[0010] The present invention has been devised in view of the above-mentioned problems, and has an object to provide a flux-cored wire for gas-shielded arc welding of 490-550 MPa class steel, which generates less fume and spatter, particularly when welding at a high current, has excellent welding workability, and can provide a weld metal having good mechanical properties even under welding conditions of high heat input and high interpass temperature. [Means for solving the problem]
[0011] The present inventors have conducted detailed studies on the component composition of flux-cored wire for gas-shielded arc welding, which is used for high-current welding of 490 to 550 MPa class steel, and further for high heat input and high interpass temperatures, and which provides a weld metal with appropriate strength and toughness, a stable arc, low fume and spatter generation, excellent bead shape and appearance, and good welding workability such as prevention of welding defects.
[0012] As a result, it was found that the amount of fume generated can be reduced even under high current welding conditions by reducing the content of C in the steel sheath, S in the wire, and Na oxide.
[0013] Regarding other welding workability, it was found that the arc can be stabilized and the amount of spatter reduced by adjusting the total amount of C in the wire, the F equivalent value of metal fluorides, and the K2O equivalent value of K oxides to an appropriate amount, and that the bead shape and appearance can be improved by adjusting the total amount of Si oxides in SiO2 equivalent value.
[0014] Furthermore, in order to achieve appropriate strength and stable toughness of the weld metal even under high-current welding conditions, it was discovered that it is effective to minimize the amount of oxides in the wire, which are slag-forming agents, and to optimize the amounts of the alloy components C, Si, Mn, Cu, and Ti.
[0015] They also discovered that by adjusting the amount of Mo and B in the wire to an appropriate level, it is possible to increase the strength of the weld metal without reducing its toughness, even under welding conditions of large heat input and high interpass temperatures.
[0016] Furthermore, it was also found that the toughness of the weld metal can be further improved by adjusting the amounts of Al and Mg in the wire to appropriate levels.
[0017] That is, the gist of the present invention is a flux-cored wire for gas shielded arc welding, which is made by filling a steel sheath with flux, the C content in the steel sheath is 0.02% or less in mass% relative to the total mass of the steel sheath, the total content of the steel sheath and the flux is 0.01-0.08% C, 0.4-1.4% Si, 1.5-3.0% Mn, 0.05-0.5% Cu, 0.1-0.3% Ti, and 0.007% or less S, in mass% relative to the total mass of the wire. and further characterized in that the flux contains, in mass % relative to the total mass of the wire, metal fluorides: a total of 0.005 to 0.10% in F conversion value, silicon oxides: a total of 0.01 to 0.2% in SiO2 conversion value, potassium oxides: a total of 0.01 to 0.10% in K2O conversion value, sodium oxides: a total of 0.01% or less in Na2O conversion value, and the balance consisting of Fe in the steel sheath, iron powder added to adjust the composition, the Fe content of the iron alloy, and unavoidable impurities.
[0018] The wire further contains, in mass % relative to the total mass of the wire, 0.5% or less of Mo and 0.010% or less of B in terms of the total mass of the steel sheath and flux.
[0019] The flux-cored wire for gas-shielded arc welding further contains, in mass % relative to the total mass of the wire, 0.25% or less of either or both of Al and Mg in total in terms of the total mass of the steel sheath and flux. Effect of the Invention
[0020] According to the flux-cored wire for gas-shielded arc welding to which the present invention is applied and configured as described above, when welding 490 to 550 MPa class steel, particularly when welding with a high current, the amount of fume and spatter generated is small, the arc stability is good, the bead appearance and shape are excellent, and the amount of slag generated is small, thereby preventing welding defects, and other welding workability is good. Furthermore, even under welding conditions of large heat input and high interpass temperature, the strength and toughness of the weld metal are sufficiently ensured, and high-quality weld metal can be obtained with high efficiency. [Brief description of the drawings]
[0021] [Figure 1] FIG. 1(a) is a diagram showing a state in which the arc is stable, and FIG. 1(b) is a diagram showing a state in which the arc is unstable. [Diagram 2] FIG. 13 illustrates an example of evaluating arc stability by continuously measuring voltage fluctuations. [Diagram 3] FIG. 3(a) is a diagram showing an example of a defective bead appearance and shape in a V-shaped groove, and FIG. 3(b) is a diagram showing an example of the bead appearance and shape when viewed from above. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] The components of the flux-cored wire for gas-shielded arc welding according to the present invention and the reasons for limiting the compositions are described below. The content of each component is expressed in mass%, and the mass% is simply expressed as %.
[0023] [C in steel sheath: 0.02% or less by mass relative to the total mass of the steel sheath] By keeping the C content in the steel sheath to 0.02% or less of the total mass of the steel sheath, the phenomenon of droplet bursting that occurs during droplet transfer in CO2 gas shielded arc welding is suppressed, the molten pool and arc state are stabilized, and the amount of spatter and fume generated is reduced. Therefore, the C content in the steel sheath to the total mass of the steel sheath is set to 0.02% or less.
[0024] Hereinafter, the content of each component will be shown as mass% relative to the total mass of the flux-cored wire, and the mass% will be simply expressed as %.
[0025] [Total of steel sheath and flux: C: 0.01-0.08%] C has the effect of improving the strength of the weld metal. If C is less than 0.01%, sufficient weld metal strength cannot be obtained. On the other hand, if C exceeds 0.08%, the strength of the weld metal increases and the toughness decreases. Therefore, the total C content of the steel sheath and flux is set to 0.01 to 0.08%. Note that C can be added from the components contained in the steel sheath, as well as from the flux, metal powder, alloy powder, etc.
[0026] [Si: 0.4~1.4% in total for steel sheath and flux] Silicon is a deoxidizing agent and adjusts the amount of oxygen in the weld metal. Silicon also has the effect of improving the strength of the weld metal. If the amount of silicon is less than 0.4%, the deoxidization is insufficient, the strength of the weld metal is low, and the toughness is reduced. On the other hand, if the amount of silicon exceeds 1.4%, the strength of the weld metal becomes excessively high, and the toughness cannot be obtained stably. If the amount of silicon exceeds 1.4%, the amount of slag generated during welding increases, and welding defects such as slag inclusion are likely to occur. Therefore, the total amount of silicon in the steel sheath and the flux is set to 0.4 to 1.4%. In addition to the components contained in the steel sheath, silicon can be added from the flux as metal silicon, Fe-Si, Fe-Si-Mn, and other alloy powders.
[0027] [Mn: 1.5-3.0% in total for steel sheath and flux] Mn has the effect of improving the toughness and strength of the weld metal. If the Mn content is less than 1.5%, the strength of the weld metal decreases, and the toughness decreases. On the other hand, if the Mn content exceeds 3.0%, the strength of the weld metal increases, and the toughness cannot be obtained stably. Furthermore, if the Mn content exceeds 3.0%, the amount of slag generated during welding increases, and welding defects such as slag inclusion become more likely to occur. Therefore, the total Mn content of the steel sheath and the flux is set to 1.5 to 3.0%. Note that Mn can be added from the components contained in the steel sheath, as well as from alloy powders such as metal Mn, Fe-Mn, and Fe-Si-Mn.
[0028] [Cu: 0.05~0.5% in total for steel sheath and flux] Cu has a precipitation strengthening effect, lowers the transformation temperature, refines the structure of the weld metal, and stabilizes the toughness. If Cu is less than 0.05%, this effect cannot be obtained, and stable toughness of the weld metal cannot be obtained. On the other hand, if Cu exceeds 0.5%, precipitation embrittlement occurs, the toughness of the weld metal decreases, and hot cracking becomes more likely to occur. Therefore, the total Cu content of the steel sheath and flux is set to 0.05 to 0.5%. Cu can be added from the components contained in the steel sheath and the Cu plating applied to the surface of the steel sheath, as well as from metallic Cu from the flux and alloy powder such as Fe-Si-Cu.
[0029] [Ti: 0.1-0.3% in total for steel sheath and flux] Ti stabilizes the arc, especially during high current welding and high heat input / high interpass temperature welding, and acts as a deoxidizer, while also generating fine Ti oxides in the weld metal, which improves the toughness of the weld metal. If Ti is less than 0.1%, this effect cannot be obtained, and the arc becomes unstable during high current welding and high heat input / high interpass temperature welding, and the toughness of the weld metal decreases. On the other hand, if Ti exceeds 0.3%, Ti precipitates increase in the weld metal, which reduces the toughness. Therefore, the total Ti content of the steel sheath and flux is 0.1-0.3%. In addition to the components contained in the steel sheath, Ti can be added from metallic Ti from the flux, alloy powder such as Fe-Ti, etc.
[0030] [Sulfur (Steel sheath and flux) combined: 0.007% or less] S exists as an impurity in the metal powder and ferroalloy in the steel sheath and flux, and even small amounts have the effect of lowering the surface tension of the droplets. If S is less than 0.007%, the droplets become larger during welding, suppressing metal evaporation in the arc atmosphere and suppressing fume generation. On the other hand, if S exceeds 0.007%, the droplets become smaller and the surface area of the droplets becomes larger, especially during welding with high current and welding with high heat input and high interpass temperature, causing metal to evaporate in the arc atmosphere and increasing the amount of fume generation. Therefore, the total S content of the steel sheath and flux should be 0.007% or less.
[0031] [Metal fluorides in flux: 0.005-0.10% in total in F conversion value] Metal fluorides have the effect of concentrating and stabilizing the arc. If the total F-equivalent value of the metal fluorides is less than 0.005%, this effect is not obtained, the arc becomes unstable, and the amount of spatter generation increases. On the other hand, if the total F-equivalent value of the metal fluorides exceeds 0.10%, the arc becomes unstable, and the amount of spatter generation increases. Therefore, the total F-equivalent value of the metal fluorides contained in the flux is 0.005 to 0.10%. Note that the metal fluorides can be added from CaF2, NaF, LiF, MgF2, K2SiF6, Na3AlF6, AlF3, etc. from the flux, and the F-equivalent value is the total amount of F contained therein.
[0032] [Si oxide in flux: 0.01-0.2% in total in terms of SiO2] The silicon oxide in the flux has the effect of increasing the viscosity of the molten slag, improving the slag encapsulation, improving the conformity of the bead toe, and improving the bead appearance and shape. If the total of the silicon oxides in terms of SiO2 is less than 0.01%, the conformity of the weld bead toe will be poor, and the bead appearance and shape will be poor. On the other hand, if the total of the silicon oxides in terms of SiO2 exceeds 0.2%, the amount of oxygen in the weld metal will increase and the toughness will decrease. Also, if the total of the silicon oxides in terms of SiO2 exceeds 0.2%, the amount of slag will increase, and welding defects such as slag inclusion will easily occur. Therefore, the total of the silicon oxides in terms of SiO2 contained in the flux should be 0.01 to 0.2%. The silicon oxide can be added from the solid components of water glass made of silica sand, orthoclase, and potassium silicate from the flux.
[0033] [K oxides in flux: 0.01-0.10% in total converted to K2O] K oxide has the effect of stabilizing the arc. If the total of the K2O equivalent value of K oxide is less than 0.01%, the arc becomes unstable and the amount of spatter generation increases. On the other hand, if the total of the K2O equivalent value of K oxide exceeds 0.10%, the arc becomes unstable and the amount of spatter generation increases. Also, if the total of the K2O equivalent value of K oxide exceeds 0.10%, the amount of slag generated during welding increases, and welding defects such as slag inclusion become more likely to occur. Therefore, the total of the K2O equivalent value of K oxide contained in the flux is 0.01 to 0.10%. K oxide can be added from a powder of orthoclase, a solid component of water glass made of potassium silicate, or the like.
[0034] [Sodium oxides in flux: Total Na2O equivalent value 0.01% or less] If the total Na2O equivalent value of Na oxide exceeds 0.01%, the amount of fume generated increases, especially during welding with high current and welding with high heat input and high interpass temperature. Therefore, the total Na2O equivalent value of Na oxide contained in the flux should be 0.01% or less. Note that Na oxide is not an essential component, and the content may be 0%.
[0035] [Total of steel sheath and flux: Mo: 0.5% or less] Mo is important for ensuring the strength of the weld metal under welding conditions of high heat input and high interpass temperature. However, if Mo exceeds 0.5%, the strength of the weld metal becomes excessively high and toughness cannot be obtained stably. Therefore, the total Mo content of the steel sheath and flux should be 0.5% or less. In order to ensure the strength of the weld metal under welding conditions of high heat input and high interpass temperature, Mo is preferably 0.15% or more. In addition to being a component contained in the steel sheath, Mo can be added from metallic Mo powder from the flux.
[0036] [B: 0.010% or less in total for steel sheath and flux] B has the effect of suppressing the formation of grain boundary ferrite at the grain boundaries of the weld metal and improving toughness under welding conditions of high heat input and high interpass temperature. However, if B exceeds 0.010%, the grain boundaries become embrittled, the toughness decreases, and hot cracking becomes more likely to occur. Therefore, the total B content of the steel sheath and flux is 0.010% or less. In order to refine the structure of the weld metal and improve its toughness under welding conditions of high heat input and high interpass temperature, B is preferably 0.0015% or more. In addition to the components contained in the steel sheath, B can be added from alloy powders such as Fe-Si-B and Fe-Mn-B.
[0037] [Total of Al and / or Mg in steel sheath and flux: 0.25% or less] Al and Mg are strong deoxidizers that reduce oxygen in the weld metal and increase the toughness of the weld metal. However, if the total of either or both of Al and Mg exceeds 0.25%, a strong oxidation reaction occurs in the arc during welding, resulting in a large amount of fume and spatter generation. Therefore, the total of either or both of Al and Mg in the steel sheath and flux should be 0.25% or less. In order to reduce oxygen in the weld metal and increase the toughness of the weld metal, it is preferable that the total of either or both of Al and Mg is 0.05% or more. Al and Mg can be added from alloy powders such as metallic Al, Fe-Al, metallic Mg, and Al-Mg.
[0038] The flux-cored wire for gas-shielded arc welding of the present invention has a structure in which a steel sheath is formed into a pipe shape and filled with flux. The types of wire can be roughly divided into a wire with no seam in the steel sheath obtained by welding the seam of the formed steel sheath, and a wire with a seam in the steel sheath where no welding is performed on the seam. In the present invention, any cross-sectional structure of wire can be used, but a wire with a seam in the steel sheath is prone to cold cracking when the strength of the weld metal increases, so it is necessary to use raw materials with a low moisture content. On the other hand, a wire with no seam in the steel sheath is more preferable because it can be heat-treated to reduce the total hydrogen content in the wire, and the flux does not absorb moisture after production, so that the diffusible hydrogen content of the weld metal can be reduced and the cold cracking resistance can be improved.
[0039] The remainder of the flux-cored wire for gas-shielded arc welding of the present invention is Fe in the steel sheath, iron powder added for adjusting the composition, Fe content in iron alloy powder such as Fe-Si, Fe-Mn, Fe-Ti alloy, and inevitable impurities. The inevitable impurities are not particularly specified, but from the viewpoint of hot cracking and toughness of the weld metal, P: 0.05% or less is preferable.
[0040] Further, the flux filling rate is not particularly limited, but is preferably 8 to 20% of the total mass of the wire from the viewpoint of productivity. EXAMPLES
[0041] The effects of the present invention will now be described in more detail with reference to examples.
[0042] Using a steel sheath with the chemical composition shown in Table 1, the steel sheath was formed into a U-shape, filled with flux at a filling rate of 10 to 15% and formed into a C-shape, after which the seams of the steel sheath were welded to form a pipe and drawn to produce flux-cored wires with the various compositions shown in Table 2. The diameter of the prototype wire was 1.4 mm.
[0043] [Table 1]
[0044] [Table 2]
[0045] Using the prototype flux-cored wires shown in Table 2, we investigated the amount of fume generation, the amount of spatter generation, the arc stability, the bead appearance and shape, the presence or absence of defects by X-ray transmission testing, and the weld metal performance.
[0046] The amount of fume generated was calculated as a value per unit time (mg / min) by measuring the weight of fumes generated during one minute of welding in accordance with JIS Z 3930. The fume measurement was the average value of three measurements taken under the construction conditions of Condition No. T1 shown in Table 3, and a value of 600mg / min or less was considered good.
[0047] The amount of spatter generated was calculated as a value per unit time (g / min) by measuring the weight of spatter generated during 1 minute of welding using a copper collection box. The spatter was measured as the average value of 5 measurements taken under the construction conditions of Condition No. T1 shown in Table 3, and a value of 1.5g / min or less was considered good.
[0048] The welding workability and weld metal performance were investigated by conducting a multi-layer weld metal test using a test piece with a 35° V groove, a root gap of 8 mm, and a backing metal under the construction conditions of Condition No. T2 shown in Table 3, and investigating the arc stability during welding and the bead appearance and shape.
[0049] Arc stability indicates the degree of stability of the arc. In other words, this arc stability indicates the degree to which the arc length and directivity of the arc 2 generated from the flux-cored wire 1 are constant, as shown in Figure 1. As shown in Figure 1(a), if there is no fluctuation in the arc length or arc spread of the arc 2 due to voltage fluctuation during welding and stable welding is possible, it can be determined that the arc 2 is stable. On the other hand, as shown in Figure 1(b), if the arc length and spread of the arc 2 fluctuate during welding and are unstable, it can be determined that the arc 2 is unstable. In general, when the arc is unstable, the bead shape and appearance deteriorate.
[0050] Such arc stability appears as voltage fluctuation during welding. For this reason, in this embodiment, the stability of this arc is evaluated by continuously measuring the voltage fluctuation and measuring the magnitude of the fluctuation. As an example of judging the determinability of the arc, as shown in the time-series voltage fluctuation chart in FIG. 2(a), when a threshold value is set to ±1V from the average voltage, the time during which the voltage fluctuation exceeds the threshold value is determined. Less than 10%The arc is deemed stable when the voltage fluctuation exceeds the threshold value of ±1V relative to the average voltage, as shown in the time-series voltage fluctuation chart in Figure 2(b), if the time during which the voltage fluctuation exceeds the threshold value exceeds 10% of the measurement time, the arc is deemed unstable. Regarding the investigation of the bead appearance and shape, if the bead appearance and shape are beautiful and uniform, it is judged as good, and if the bead appearance and shape are partially or entirely irregular and unstable, it is judged as bad. Examples of poor bead appearance and shape include undercuts in which the base material 3 is scraped off by the arc, as shown in the R-shaped groove in Figure 3(a), and overlaps, both of which require grinding after welding. As shown in Figure 3(b) when the bead is viewed from above, cases where the bead waveform is irregular or the bead toe is irregular are also judged as poor bead appearance and shape. In this embodiment, the bead appearance and shape is judged to be good or bad by visual observation, and if there is even one undercut or overlap, it is judged to be bad.
[0051] After welding was completed, the backing metal was removed and an X-ray test was performed. The X-ray test was performed based on the radiographic test method for steel welded joints shown in JIS Z 3104:1995, and if no flaws were found, it was determined to be defect-free. In addition, A0 tensile test pieces and impact test pieces were taken from the weld metal to investigate the mechanical properties.
[0052] Strength was evaluated as tensile strength of 490 to 690 MPa, and toughness was evaluated as Charpy impact tests were performed on five pieces at 0°C, with an average absorbed energy of 80 J or more and a minimum of 60 J or more being considered good. The results are summarized in Table 4.
[0053] [Table 3]
[0054] [Table 4]
[0055] In Tables 2 and 4, wire symbols W1 to W10 are examples of the present invention, and wire symbols W11 to W20 are comparative examples. Wires W1 to W10, which are examples of the present invention, have appropriate contents of C in the steel sheath, C, Si, Mn, Ti, and S in the flux-cored wire, and appropriate amounts of the total F-equivalent value of metal fluorides in the flux, the total SiO2-equivalent value of Si oxides, the total K2O-equivalent value of K oxides, and the total Na2O-equivalent value of Na oxides, so that even under high-current welding conditions, the amount of fume and spatter generation was small, the arc was stable, the bead appearance and shape were good, there were no welding defects, and the tensile strength of the weld metal and the average and minimum absorbed energy were both good.
[0056] In addition, the wires W3, W5, W7 and W9, which have appropriate amounts of either or both of Al and Mg, achieved an average absorbed energy of 100 J or more in the weld metal, which was an extremely satisfactory result.
[0057] In the comparative example, wire symbol W11 had a large amount of C in the steel sheath symbol F4, so the amount of fume and spatter was large. Also, because it had a large amount of Ti, the absorbed energy of the weld metal was low. In addition, because the total amount of one or both of Al and Mg was small, the effect of improving the absorbed energy of the weld metal was not obtained.
[0058] The wire symbol W12 had a low C content in the flux-cored wire, so the tensile strength of the weld metal was low. In addition, the total SiO2 equivalent value of Si oxide was high, so slag inclusion defects occurred and the absorbed energy of the weld metal was low. Furthermore, the total of either or both of Al and Mg was high, so the amount of fume and spatter generation was high.
[0059] The wire symbol W13 had a high C content in the flux-cored wire, so the tensile strength of the weld metal was high and the absorbed energy was low. Also, the total F-converted value of the metal fluorides was low, so the arc was unstable and a large amount of spatter was generated.
[0060] Wire symbol W14 has a low Si content, so the tensile strength of the weld metal was low and the absorbed energy was also low. Also, the total F-converted value of the metal fluorides was high, so the arc was unstable and a large amount of spatter was generated.
[0061] Wire symbol W15 has a high Si content, so slag inclusion defects occurred, the tensile strength of the weld metal was high, and the minimum absorbed energy was low. In addition, because the total of either or both of Al and Mg was low, the effect of improving the absorbed energy of the weld metal was not obtained.
[0062] Wire symbol W16 had a low Mn content, so the tensile strength of the weld metal was low and the absorbed energy was also low. Also, the total SiO2 equivalent value of Si oxide was low, so the bead appearance and shape were poor.
[0063] Wire symbol W17 has a high Mn content, so the tensile strength of the weld metal is high and the minimum absorbed energy is low. Also, because of the high Mn content, slag inclusion defects occurred. Furthermore, because of the high S content, a large amount of fume was generated.
[0064] Wire symbol W18 had a low Cu content, so the minimum absorbed energy of the weld metal was low.
[0065] Wire symbol W19 has a high Cu content, so the absorbed energy of the weld metal was low. Also, because of the high Cu content, crater cracks occurred. Furthermore, because the total K2O equivalent value of K oxide was low, the arc was unstable and a large amount of spatter was generated.
[0066] The wire symbol W20 had a low Ti content, which resulted in an unstable arc and low absorbed energy in the weld metal. In addition, the total K2O equivalent value of K oxide was high, which resulted in slag inclusion defects. EXAMPLES
[0067] As in Example 1, a steel sheath having the chemical composition shown in Table 1 was formed into a U-shape, filled with flux at a filling rate of 10 to 15% and formed into a C-shape, after which the joints of the steel sheath were welded to form a pipe and drawn to produce flux-cored wires having the various compositions shown in Table 5. The diameter of the wire produced was 1.4 mm.
[0068] [Table 5]
[0069] Using the prototype flux-cored wires shown in Table 5, the amount of fume generation, the amount of spatter generation, the arc stability, the bead appearance and shape, the presence or absence of defects by X-ray transmission testing, and the weld metal performance were investigated.
[0070] The amount of fume generated was calculated as a value per unit time (mg / min) by measuring the weight of fumes generated during one minute of welding in accordance with JIS Z 3930. The fume measurement was the average value of three measurements taken under the construction conditions of Condition No. T1 shown in Table 3, and a value of 600mg / min or less was considered good.
[0071] The amount of spatter generated was calculated as a value per unit time (g / min) by measuring the weight of spatter generated during 1 minute of welding using a copper collection box. The spatter was measured as the average value of 5 measurements taken under the construction conditions of Condition No. T1 shown in Table 3, and a value of 1.5g / min or less was considered good.
[0072] Welding workability and weld metal performance were investigated by conducting multi-layer weld metal tests using specimens with a 35° groove and a root gap of 8 mm and backing metal under the high heat input and high interpass temperature conditions of Condition No. T3 shown in Table 3. The arc stability during welding and the bead appearance and shape were investigated. After welding was completed, the backing metal was removed and an X-ray examination was performed. A0 tensile test pieces and impact test pieces were also taken from the weld metal to investigate the mechanical properties.
[0073] Strength was evaluated as tensile strength of 520 to 720 MPa, and toughness was evaluated as Charpy impact tests were performed on five pieces at 0°C, with an average absorbed energy of 80 J or more and a minimum of 60 J or more being considered good. The results are summarized in Table 6.
[0074] [Table 6]
[0075] In Tables 5 and 6, wire symbols W21 to W25 are examples of the present invention, and wire symbols W26 to W30 are comparative examples. Wires W21 to W25, which are examples of the present invention, have appropriate contents of C in the steel sheath, C, Si, Mn, Ti, S, Mo, and B in the flux-cored wire, and appropriate amounts of the total F-equivalent value of metal fluorides in the flux, the total SiO2-equivalent value of Si oxides, the total K2O-equivalent value of K oxides, and the total Na2O-equivalent value of Na oxides, so that even under welding conditions of large heat input and high interpass temperature, the amount of fume and spatter generation was small, the arc was stable, the bead appearance and shape were good, there were no welding defects, and the tensile strength of the weld metal and the average and minimum absorbed energy were both good.
[0076] In addition, the wires W21 and W23, which have appropriate amounts of either or both of Al and Mg, achieved an average absorbed energy of 100 J or more in the weld metal, which was an extremely satisfactory result.
[0077] In the comparative example, wire symbol W26 had a low tensile strength of the weld metal because the flux-cored wire contained a small amount of C. In addition, because the wire contained a small amount of Mo, the effect of improving the tensile strength of the weld metal was not obtained.
[0078] Wire symbol W27 generated a large amount of fumes because it contained a lot of S. It also contained a lot of Mo, so the tensile strength of the weld metal was high and the minimum absorbed energy was low. In addition, because the total of one or both of Al and Mg was low, the effect of improving the absorbed energy of the weld metal was not obtained.
[0079] The wire symbol W28 had a low Ti content, which resulted in an unstable arc and low absorbed energy in the weld metal. In addition, the wire had a low B content, which did not improve the absorbed energy in the weld metal.
[0080] Wire symbol W29 had a large total Na2O equivalent value of Na oxide, so it generated a large amount of fumes. Also, because it contained a lot of B, crater cracks occurred. Furthermore, because it contained a lot of B, the absorbed energy of the weld metal was low.
[0081] Wire symbol W30 has a low Mn content, so the tensile strength of the weld metal was low and the absorbed energy was also low. In addition, because it has a low Mo content, the effect of improving the tensile strength of the weld metal was not obtained. [Explanation of symbols]
[0082] 1 Flux-cored wire 2. Arc 3 Base material
Claims
1. A flux-cored wire for gas shielded arc welding, which is made by filling a steel sheath with flux, The C content in the steel sheath is 0.02% or less by mass relative to the total mass of the steel sheath, The mass percentage of the total wire mass is the sum of the steel sheath and flux. C: 0.01-0.08%, Si: 0.4-1.4%, Mn: 1.5-3.0%, Cu: 0.05-0.5%, Ti: 0.1 to 0.3%; S: 0.007% or less; Furthermore, in the flux, the mass percentage relative to the total mass of the wire is: Metal fluorides: 0.005 to 0.10% in total F conversion value, Si oxide: SiO 2 The total conversion value is 0.01 to 0.2%, K oxide: K 2 Contains 0.01 to 0.10% in total converted into O. Na oxide: Na 2 The total O equivalent value is 0.01% or less, A flux-cored wire for gas-shielded arc welding, the balance of which consists of Fe in a steel sheath, iron powder added for adjusting the composition, Fe in an iron alloy, and unavoidable impurities.
2. The mass percentage of the total wire mass is the sum of the steel sheath and flux. Mo: 0.5% or less, 2. The flux-cored wire for gas shielded arc welding according to claim 1, further comprising B: 0.010% or less.
3. The mass percentage of the total wire mass is the sum of the steel sheath and flux.
3. The flux-cored wire for gas-shielded arc welding according to claim 1, further comprising one or both of Al and Mg: 0.25% or less in total.
Citation Information
Patent Citations
Gas shield arc welding metal type flux cored wire
JP1995276077A
Gas shield arc welding wire
JP1998230387A
Solid wire for carbon-dioxide shielded arc welding
JP2002346789A
Wire for gas shielded arc welding and method for welding the same
JP2004098143A
Steel wire for carbon dioxide gas-shielded arc welding
JP2005169415A